Noise and sound in the intensive care unit: a cohort study - A. Tahvili; A. Waite; T. Hampton; I. Welters; P. J. Lee (Scientific Reports)
Abstract Intensive care units (ICUs) are acknowledged for their propensity for noise, often exhibiting higher sound levels on average than other departments. This is mainly ascribed to a high concentration of medical devices and staff, creating an acoustic environment characterised by a high level of staff activity and a concoction of alarms from therapeutic and monitoring devices. Excessive noise in ICUs has been associated with adverse health effects and human factor impacts acknowledged to negatively affect both patients and healthcare providers. This study aimed to evaluate the sound levels of the Royal Liverpool University Hospital (RLUH) ICU and compare it against recommended guidelines. Prospective sound level measurements were taken from a six-bedded bay within the RLUH ICU between 15th June and 1st July 2022. This audit focussed on sound data that equal or exceeded 87 dBA, in accordance with levels in the UK Noise Regulations. The data involved 11 patients admitted to the bay within the defined timeframe. A retrospective review of the patients’ records was conducted to identify potential noisy events during the recording period. Results revealed all LAeq and L Amax measurements exceeded the recommended guidelines. Although HSE exposure limit values were not exceeded, the lowest L Amin value recorded was 44.2 dBA and only one hour from 16 days of recording (less than 1% of the time) fell below international daytime guidelines of 45 dBA. The top documented potential causes of noise were patient repositioning/personal care, medication administration and suctioning. Sound levels in the RLUH ICU considerably exceed national and international guidelines. These findings highlight the need to address the issue of noise pollution in the ICU setting. Hospital staff should consider implementing strategies and interventions for noise reduction in ICUs.